The effect of mental training to develop shooting accuracy from jumping among youngsters of the National Center for the Nurturing of Sports Talent (Journal of the College of Basic Education, 2022)
The study aimed to prepare mental training exercises to develop the accuracy of scoring from jumping and to identify the level of development in the accuracy of scoring from jumping using exercises for the experimental group. The researcher used the experimental method, and the research sample consisted of (12) players who were divided into two groups, experimental and control, in a random way, by the lottery method. Conducting pre and post tests, the results of the experimental group's progress appeared over the control group, and (spss) was used to extract the research statistics.